MULTISENSORY APPROACH IN QURANIC LITERACY FOR DYSLEXIA LEARNERS: A SYSTEMATIC REVIEW - Anuar, Nur Liyana Athirah; Muhamad, Norhisham (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This Systematic Literature Review (SLR) examines the application of multisensory approaches in Quranic literacy instruction for learners with dyslexia, emphasizing its pedagogical, cognitive, and technological dimensions. Quranic literacy is central to Islamic education. However, dyslexic learners often struggle with decoding Arabic script and mastering phonological patterns due to weaknesses in reading fluency, phonological processing, and working memory. To address these challenges, this review synthesizes recent empirical evidence to identify instructional frameworks that can enhance inclusive Quranic learning. Guided by the PRISMA protocol, a comprehensive search was conducted across Scopus and PubMed, focusing on studies published between 2021 and 2025. The search strategy, which used keywords such as dyslexia, literacy, and multisensory, initially yielded 2,843 records that were systematically screened and refined to 28 high-quality primary studies. The findings were organized into three interconnected themes: One, Assessment and Measurement, highlighting the need for reliable screening tools and culturally adapted literacy assessments. Two, Interventions, Technologies, and Instructional Approaches, demonstrating that multisensory, technology-assisted, and structured feedback methods significantly improve reading fluency, comprehension, and learner engagement. Three, Developmental, Cognitive, and Socio-environmental Factors, examining the roles of phonological awareness, motivation, family literacy practices, and teacher competencies in shaping learning outcomes. Overall, the review shows that multisensory instruction integrating visual, auditory, kinesthetic, and tactile modalities provides substantial benefits for dyslexic learners by supporting neural integration and enhancing engagement with Quranic text. The review concludes that multisensory approaches bridge cognitive science with Islamic pedagogy to support evidence-based teaching.